Acute Changes in Arterial Stiffness with Palatinose Versus Glucose Intake in Elderly - Kobayashi, Ryota; Sato, Kaori; Sakazaki, Miki; Nagai, Yukie; Takahashi, Toshihiko; Asaki, Kenji; Iwanuma, Soichiro; Ohashi, Nobuyuki; Hashiguchi, Takeo (Cardiology and Cardiovascular Medicine, 2020)
Background: We assessed acute effects of palatinose (isomaltulose) consumption on arterial stiffness. Increased arterial stiffness due to elevated postprandial blood glucose levels increases the risk of cardiovascular disease. Palatinose appears to suppress an increase in BG levels while securing energy, and might decrease acute increases in arterial stiffness during hyperglycemia. However, the acute effects of palatinose consumption on arterial stiffness are unknown. Methods: Ten older adults had two interventions in the following cross-over design: (i) ingestion of 25 g of glucose solution (GSI trial) and (ii) ingestion of 25 g of palatinose solution (PSI trial). Participants fasted for 12 h and then visited the laboratory. We assessed brachialankle (ba) and heartbrachial (hb) pulse wave velocity (PWV), the cardio-ankle vascular index (CAVI), brachial and ankle blood pressure, heart rate, and blood glucose levels at baseline (before ingestion) and 30, 60, and 90 min after ingestion. Results: Changes in baPWV, hbPWV, the CAVI, and ankle systolic blood pressure were significantly increased from baseline at 30, 60, and 90 min after ingestion in the GSI trial (p < 0.05), but not in the PSI trial. The changes in baPWV, hbPWV, and CAVI were significantly lower after ingestion in the PSI trial compared with the GSI trial. Blood glucose levels were significantly lower at 30 and 60 min after ingestion in the PSI trial compared with the GSI trial (p < 0.01). Conclusions: We conclude that arterial stiffness may increase after glucose ingestion, but it is not elevated after palatinose ingestion.